2021
DOI: 10.1186/s12884-021-04234-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors associated with pregnant women’s experiences of material hardship during COVID-19: a cross-sectional Qualtrics survey in the United States

Abstract: Background The COVID-19 pandemic has exacerbated the financial insecurity of women and their families globally. Some studies have explored the impact of financial strain among pregnant women, in particular, during the pandemic. However, less is known about the factors associated with pregnant women’s experiences of material hardship. Methods This cross-sectional study used a non-probability sample to examine the factors associated with pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The poor coverage of health insurance and financial problems forced people to postpone or avoid the institutional services related to pregnancy antenatal care ( Abufaraj et al, 2021 ; Johnson, 2021 ), child care ( Vance et al, 2021 ), and postponement of childbearing intentions ( Malicka et al, 2021 ). Rapid coverage of health insurance policies ( Abufaraj et al, 2021 ), counseling for childbearing and family planning, social security schemes, financial support for pregnant women ( Johnson, 2021 ), and neonatal care and improving public health facilities ( Letourneau et al, 2021 ) are some health-related measures to cope with these challenges. Healthcare workers struggled for better packages matching their efforts for defending COVID-19, especially nurses ( Akkuş et al, 2021 ; Cho et al, 2021 ); orthopedic surgeons ( Attarde et al, 2021 ); otorhinolaryngologists ( Dosemane et al, 2021 ); and dentists ( Kumar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The poor coverage of health insurance and financial problems forced people to postpone or avoid the institutional services related to pregnancy antenatal care ( Abufaraj et al, 2021 ; Johnson, 2021 ), child care ( Vance et al, 2021 ), and postponement of childbearing intentions ( Malicka et al, 2021 ). Rapid coverage of health insurance policies ( Abufaraj et al, 2021 ), counseling for childbearing and family planning, social security schemes, financial support for pregnant women ( Johnson, 2021 ), and neonatal care and improving public health facilities ( Letourneau et al, 2021 ) are some health-related measures to cope with these challenges. Healthcare workers struggled for better packages matching their efforts for defending COVID-19, especially nurses ( Akkuş et al, 2021 ; Cho et al, 2021 ); orthopedic surgeons ( Attarde et al, 2021 ); otorhinolaryngologists ( Dosemane et al, 2021 ); and dentists ( Kumar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on Jordan related to the gender disparities and healthcare facilities during COVID-19 has found that the limited coverage of the health insurance coverage, reduced payments, denial of payment to women during the COVID-19, and job losses affected the financial wellbeing and the pregnant women were unable to undertake the antenatal care ( Abufaraj et al, 2021 ; Mecik et al, 2022 ; Stevenson et al, 2022 ). The financial challenges of pregnant women during COVID-19 were also identified in the study ( Johnson, 2021 ). Child care is another important segment affected by the financial distress by COVID-19 ( Vance et al, 2021 ).…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there were no studies on the level of financial abuse or elements of the patriarchal form of relationships in families in Latvia, but our theoretical assumption is that it is likely that financial dependence during periods of economic inactivity is an aggravating factor for the development of mental health problems. For example, one recent study during the COVID-19 pandemic in the United States found that the percentage of women who experienced at least one form of economic violence while on maternity leave was quite high (approximately 65%) ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…A smaller body of research has looked specifically at the effects of economic abuse during pregnancy or postpartum. Among a sample of pregnant women, Johnson (2021) found that economic abuse was significantly associated with material hardship. Gürkan et al (2020) found that experiencing economic abuse during pregnancy was associated with increased reported tiredness/fatigue and mental health symptomology; Kapiga et al (2017) also found a significant association between economic abuse and poor mental health during pregnancy.…”
Section: Introductionmentioning
confidence: 99%